1999
DOI: 10.1083/jcb.145.7.1407
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Import of the TATA-binding Protein: Mediation by the Karyopherin Kap114p and a Possible Mechanism for Intranuclear Targeting

Abstract: Binding of the TATA-binding protein (TBP) to the promoter is the first and rate limiting step in the formation of transcriptional complexes. We show here that nuclear import of TBP is mediated by a new karyopherin (Kap) (importin) family member, Kap114p. Kap114p is localized to the cytoplasm and nucleus. A complex of Kap114p and TBP was detected in the cytosol and could be reconstituted using recombinant proteins, suggesting that the interaction was direct. Deletion of the KAP114 gene led to specific mislocali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
146
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(153 citation statements)
references
References 62 publications
(143 reference statements)
7
146
0
Order By: Relevance
“…The localization of GR-GFP was monitored in 14 yeast strains each deficient in a different nuclear transport receptor: CRMI (Stade et al, 1997), CSEI (Xiao et al, 1993), Kap95 (Iovine et al, 1995), Kap104 (Aitchison et al, 1996), Kap123 (Seedorf and Silver, 1997), LOS1 (Hopper et al, 1980), MSN5 (Kaffman et al, 1998a), MTR10 (Kadowaki et al, 1994), NMD5 (He and Jacobson, 1995), PSEI (Seedorf and Silver, 1997), SRP1 (Yano et al, 1992), SXM1 (Seedorf and Silver, 1997), Kap114 (Morehouse et al, 1999;Pemberton et al, 1999), and PDR6 (Titov and Blobel, 1999). Yeast strains PSY580, pse1-1, PSY1200, and PSY902 have been described (Seedorf and Silver, 1997).…”
Section: Yeast Strains Handling Transformations and Localization Smentioning
confidence: 99%
See 1 more Smart Citation
“…The localization of GR-GFP was monitored in 14 yeast strains each deficient in a different nuclear transport receptor: CRMI (Stade et al, 1997), CSEI (Xiao et al, 1993), Kap95 (Iovine et al, 1995), Kap104 (Aitchison et al, 1996), Kap123 (Seedorf and Silver, 1997), LOS1 (Hopper et al, 1980), MSN5 (Kaffman et al, 1998a), MTR10 (Kadowaki et al, 1994), NMD5 (He and Jacobson, 1995), PSEI (Seedorf and Silver, 1997), SRP1 (Yano et al, 1992), SXM1 (Seedorf and Silver, 1997), Kap114 (Morehouse et al, 1999;Pemberton et al, 1999), and PDR6 (Titov and Blobel, 1999). Yeast strains PSY580, pse1-1, PSY1200, and PSY902 have been described (Seedorf and Silver, 1997).…”
Section: Yeast Strains Handling Transformations and Localization Smentioning
confidence: 99%
“…Two microliters of this suspension was spotted on a slide beneath a coverslip, and protein localization was assessed by fluorescence microscopy with a 100ϫ oil immersion lens on the Zeis microscope described above. For hormone withdrawal experiments, yeast were washed three times in SD medium lacking hormone and incubated at 30°C for 1 h.The localization of GR-GFP was monitored in 14 yeast strains each deficient in a different nuclear transport receptor: CRMI (Stade et al, 1997), CSEI (Xiao et al, 1993), Kap95 (Iovine et al, 1995), Kap104 (Aitchison et al, 1996), Kap123 (Seedorf and Silver, 1997), LOS1 (Hopper et al, 1980), MSN5 (Kaffman et al, 1998a, MTR10 (Kadowaki et al, 1994), NMD5 (He andJacobson, 1995), PSEI (Seedorf and Silver, 1997), SRP1 (Yano et al, 1992), SXM1 (Seedorf and Silver, 1997), Kap114 (Morehouse et al, 1999;Pemberton et al, 1999), and PDR6 (Titov and. Yeast strains PSY580, pse1-1, PSY1200, and PSY902 have been described (Seedorf and Silver, 1997).…”
mentioning
confidence: 99%
“…Indeed many essential yeast nuclear proteins appear to have more than one route into the nucleus, with the preferred route being mediated by a nonessential karyopherin (Rout et al, 1997;Pemberton et al, 1999;Mosammaparast et al, 2001Mosammaparast et al, , 2002b It has been previously shown that the TATA-binding protein is imported by the karyopherin Kap114p (Morehouse et al., 1999;Pemberton et al, 1999). However in the absence of Kap114p, other karyopherins appear to be able to take its place (Pemberton et al, 1999). Transcription of genes by RNA polymerase II (RNAP II) involves many steps, some of the earliest being the recruitment of general transcription factors and RNAP II to form the preinitiation complex (PIC; Hampsey, 1998;Hahn, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…To add to the complexity of determining which Kap imports a particular cargo, it has been shown that several proteins can be imported into the nucleus by more than one Kap (Rout et al, 1997;Jakel and Gorlich, 1998;Pemberton et al, 1999;Mosammaparast et al, 2001Mosammaparast et al, , 2002bMuhlhausser et al, 2001). Indeed many essential yeast nuclear proteins appear to have more than one route into the nucleus, with the preferred route being mediated by a nonessential karyopherin (Rout et al, 1997;Pemberton et al, 1999;Mosammaparast et al, 2001Mosammaparast et al, , 2002b It has been previously shown that the TATA-binding protein is imported by the karyopherin Kap114p (Morehouse et al., 1999;Pemberton et al, 1999). However in the absence of Kap114p, other karyopherins appear to be able to take its place (Pemberton et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation